2010
DOI: 10.1158/1535-7163.mct-09-1106
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Epithelial to Mesenchymal Transition and Acquired Resistance to Sunitinib in Patients with Renal Cell Carcinoma: Evidence from a Xenograft Study

Abstract: Tyrosine kinase inhibitors (TKI) targeting angiogenesis via inhibition of the vascular endothelial growth factor pathway have changed the medical management of metastatic renal cell carcinoma. Although treatment with TKIs has shown clinical benefit, these drugs will eventually fail patients. The potential mechanisms of resistance to TKIs are poorly understood. To address this question, we obtained an excisional biopsy of a skin metastasis from a patient with clear cell renal carcinoma who initially had a respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 29 publications
11
104
1
1
Order By: Relevance
“…direct anti-tumor effect in conjunction with the previously established anti-angiogenic activity. These observations are made evident by the fact that intratumor sunitinib levels are vastly higher than the corresponding plasma concentrations as previously reported (23,24) and confirmed by our own results (Table 1). In fact, sunitinib modulates a series of complex interactions between tumor and the surrounding tissues, thereby influencing multiple cellular processes, such as angiogenesis, cell growth, and cell survival (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…direct anti-tumor effect in conjunction with the previously established anti-angiogenic activity. These observations are made evident by the fact that intratumor sunitinib levels are vastly higher than the corresponding plasma concentrations as previously reported (23,24) and confirmed by our own results (Table 1). In fact, sunitinib modulates a series of complex interactions between tumor and the surrounding tissues, thereby influencing multiple cellular processes, such as angiogenesis, cell growth, and cell survival (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…One of these factors is hypoxia. 28,29 Several studies have demonstrated that prolonged anti-angiogenic therapy increased the expression of mesenchymal phenotypes, [30][31][32][33] and this may be due to hypoxia induced by excessive anti-angiogenesis. Other studies have also shown that hypoxia and hypoxia-inducible factor-1 alpha (HIF-1α) promote EMT in several tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of interdependent pathways have been linked to the induction of EMT, which, by definition, is a potentially transient/reversible phenotype of epithelial cancers. The reverted histologic phenotype observed in the xenografts also suggests that this escape mechanisms against anti-VEGF therapies may be transient (30,32,33).…”
Section: Wwwintechopencommentioning
confidence: 99%